Creative Cities and Brand Activation Strategies in Enhancing Reputation and Attracting Tourists - Prayudi; Ardhanariswari, Kartika Ayu; Probosari, Ninik (Graduate School of Communication Universitas Bakrie, 2024)
This study examines the impact of brand activation strategies on enhancing reputation and attracting tourists to Indonesia's creative cities. In response to the rapid growth of the creative economy and the rising importance of city branding in global competition, the research aims to evaluate how these strategies are employed to drive urban development and economic growth. Utilizing a qualitative approach, including interviews, observations, and document analysis, the study provides insights into the practical implementation of brand activation across multiple Indonesian cities. The findings suggest that effective brand activation, deeply rooted in local culture and creativity, is essential for shaping a city's identity and appeal. The research concludes that successful brand activation requires a multifaceted approach involving stakeholder collaboration, effective marketing, and a commitment to preserving cultural heritage. However, it is essential to note that this study has limitations, such as the focus on a specific region and the qualitative nature of the research. These limitations should be considered when interpreting the findings. This approach is vital for Indonesian cities establishing themselves as prominent creative hubs in the ASEAN region. The study concludes with practical recommendations for policymakers and branding professionals to strengthen city branding efforts and improve the reputation and tourist attraction of Indonesia's diverse urban landscapes.